Peran Koperasi Unit Desa (KUD) Marga Bhakti dalam Program Peremajaan Sawit Rakyat (PSR) di Desa Bagan Bhakti Kecamatan Balai Jaya Kabupaten Rokan Hilir - Devi Ayu Hardiningsih; Dadang Mashur (Pusat Riset dan Inovasi Nasional, 2023)
The rejuvenation of people's oil palm is one of the national strategic programs as an effort by the government to increase the productivity of oil palm plantations, by maintaining the area of land, so that oil palm plantations can be used optimally. To deal with the problem of palm oil that is no longer productive, the government created this people's oil palm rejuvenation program. The government gave instructions to all groups, both local government and the community, to be active and participate in the program, including the Balai Jaya sub-district, which took part in implementing the program. The Bagan Bhakti Village Government and also the Marga Bhakti Village Unit Cooperative are working together in running the program. The main problem is that the palm oil in Bagan Bhakti village is no longer productive which results in a decrease in income so that it is necessary to replant oil palm so that the economy in Bagan Bhakti Village is improving again. The purpose of this study was to determine the role of the Marga Bhakti Village Unit Cooperative and to find out what are the inhibiting factors in the people's oil palm rejuvenation program. This study uses the theory of Titik Sartika Pramono with indicators, building and developing the economic potential of members, improving the quality of human life, strengthening the people's economy, and creating and developing the country's economy. This study uses a qualitative research method with a descriptive approach, the data needed are primary data and secondary data through purposive sampling data collection techniques used, namely literature study, interviews, documentation, and observation. The results of the study indicate that the implementation of the program has been going well, there are only a few deficiencies in the program that have not been fulfilled. The inhibiting factor is the Marga Bhakti Village Unit Cooperative which has not been able to make the latest program for members who do not take part in the program to continue to support their income so that they remain good.